COMPANIES INCOME TAX COMPLIANCE AND ENFORCEMENT BEHAVIOURS IN NIGERIA. AN EMPIRICAL STUDY (Journal of Contemporary Issues in Accounting, 2022)
The study empirically examined companies’ income tax compliance and enforcement behaviours in Nigeria. Ex- post facto research design was adopted for the study. Data were collected through secondary sources from the archive of Federal Inland Revenue Service (FIRS) and the annual reports of some selected companies in Nigeria. The data analysis was done using Ordinary Least Square (OLS) regression technique with econometric software (E- view 9). The population of study consists of the one hundred and seventy (170) quoted companies operating in different sectors of the economy listed on the Nigerian stock exchange as at July, 2022. Poly-stat statistical tool was used to determine the sample size of forty- one (41) companies from a total of 170 companies. The major findings showed that enforcement methods have significant impact on compliance. It is recommended that government should channel tax revenue into projects like electricity and road network in order to increase ease of doing business in the country as these companies spends millions of naira on monthly basis for power generation.
Keywords: Companies’ income tax; Behaviors; Compliance; Enforcement